Evaluation of antioxidants capacity of non-enzymatic antioxidants and its effect in glucose level in diabetic patients - Rana Fadhil Mousa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Oxidative stress might participate in the pathophysiology of diabetes type 2. Systems of nonenzymatic antioxidants are made up of scavenging molecules that are formed endogenously.The Study Objective: This study’s aims were evaluation of the non-enzymatic antioxidants and their effectin levels of glucose among diabetic patients.Methodology: A total of eighty patients with DM type 2 and forty healthy persons (control) were enrolledwithin this study. Serum and plasma were obtained from collected blood samples. The Ferric ReducingAbility of Plasma (FRAP) method was used for detection of the total antioxidant capacity (TAC). Ellman’smethod was used to determine the level of reduced glutathione. The serum CAT activity was detected by thetechnique explained by Sinha.Results: The findings revealed that, among diabetic groups, there was a significant elevation in glycosylatedhemoglobin and glucose levels; HbA1c and FBG levels were significantly higher; MDA, NO, LPI, TAC andGSH showed significant greater values. The activity of SOD showed significantly greater mean value amongthe control group.Conclusion: The results suggest that antioxidants defense might be decreased in T2DM, as TAC levelswere decreased. The increased levels of MDA, NO, LPI, TAC and GSH were associated with oxidativestress. Assessment of GSH could help in recognition of the extent of oxidative stress in diabetes as well asprevention and control of diabetic complications.